Carbon Nanotube-Based Microwave Absorbing Materials: Research Progress on Mechanisms, Composite Systems, and Structural Design - Fu, Xiaolin; Zhen, Yimeng; Jin, Anyao; Jiang, Honghui; Qin, Xianzi; Yuan, Jing (Journal of Research in Science and Engineering, 2026)
With the rapid development of electronic information technology, electromagnetic pollution is becoming increasingly serious, and the demand for high-performance microwave absorbing materials in radar stealth and civilian electromagnetic protection is becoming more and more urgent. Carbon nanotubes (CNTs) have become a research hotspot for next-generation microwave absorbing materials due to their unique advantages such as lightweight, high conductivity, tunable dielectric properties, rich polarization loss mechanisms, and ease of composite formation. This paper systematically reviews the latest research progress of CNTs-based microwave absorbing materials. First, the absorption mechanism of CNTs is elucidated, including dielectric loss, conductivity loss, interfacial polarization, and magnetic loss introduced by magnetic modification. The control of absorption performance by structural parameters such as tube diameter, aspect ratio, degree of graphitization, defect doping, and surface functionalization is analyzed. Then, composite systems of CNTs with polymers, magnetic metals, metal oxides, and two-dimensional materials such as MXene and graphene are introduced, and the roles of one-dimensional core-shell structures, three-dimensional network structures, and hierarchical multi-scale structure designs in optimizing impedance matching and enhancing multi-loss synergy are discussed. Finally, the challenges currently faced by CNTs, such as dispersion uniformity, preparation cost, and large-scale production, are analyzed, and future development directions such as intelligent tunable absorbing materials, machine learning-aided design, and green synthesis are discussed. This review aims to provide a systematic reference for the rational design and practical application of high-performance CNT-based microwave absorbing materials.